Sistem Sistem Informasi Monitoring Penjualan Guna Pengendalian Intern: Sales Monitoring Information System for Internal Control - Nofiyani, Nofiyani (KRESNA: Jurnal Riset dan Pengabdian Masyarakat, 2021)
Sales are the lifeblood of a company, because it is from sales that profits are obtained. From these profits, it can be used to develop the business and maintain the business. To be able to develop and maintain good records and monitoring for company control, as well as a way to prevent and detect embezzlement and fraud. Information systems that support the use of information technology will improve company performance (RAD) including planning, design workshops and implementation. In the development of the system, two forms of data recording were formed including an item data entry form and a sales item entry form. As well as three reports as media monitoring, controlling goods sales activities by business owners and as a reference in evaluating and reporting prices per item of goods per transaction period.